Deskripsi Sejarah Konflik Horizontal Orang Yahudi dan Samaria - Yonatan Arifianto (Sekolah Tinggi Teologi Baptis Indonesia, 2020)
The Jews and Samaria involved in claiming one another's descendants of Abraham so that the dispute from the background of multicultural interests had an impact on the harmony of the two nations. During the intertestamental situation the upheaval still occurred. Historical studies of the feud that occurred during the intertestamental period also brought the message of harmony to trigger all the descendants of Jews and Samaritans to continue to be in hatred. That is what happened in Indonesia, there were many tribal, religious and customs sentiments which were contested so that the harmony of the plural society was tarnished. But learning from Jesus that brought change changed paradigms and teachings to love one another and live in harmony.